The Role of The Community in Combating The Covid-19 Pandemic in Indonesia - Djufri Nurachman; Dewi Purnamawati (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Corona Virus Diseases 19 (Covid-19) has become a global threat. The role of the community is very much needed to break the chain of transmission of Covid-19. This study aims to determine the role of the Indonesian people in overcoming the Covid-19 pandemic in general, health, education, and the economy. Research method: using SLR. Data is collected from Scopus and indexed journals through a science direct and Garuda-based data system. Data were analyzed using content analysis techniques. Research Results: Indonesian people have implemented health protocols in the form of using masks outside the home, complying with PSBB policies, washing hands regularly. In the health sector, supporting health workers by helping to raise funds for PPE, conducting regional quarantine. In supporting education policies during the Covid-19 period, the context of which is the government, teachers, and parents, have been with all their might and dedication to provide facilities for students in the form of data packages, relaxation of curriculum policies, elimination of National Examinations, the effectiveness of teaching and learning activities in Indonesia. during the pandemic. To respond to the economic downturn itself, the community supports the return of the Indonesian economy, such as opening small businesses online, supporting policies for providing assistance and relaxing MSME loans by submitting small businesses, supporting government policies on tax relaxation. while still paying taxes. Conclusion: In general, the Indonesian people have been quite disciplined in trying to prevent the spread of COVID-19, both in the fields of health, education, and the economy.